Peran Efektivitas Penggunaan Dana pada Hubungan Antara Kinerja Keuangan dan Tingkat Kemandirian Keuangan Rumah Sakit - Munif, Naila Rusyda; Firmansyah, Amrie (Penerbit Goodwood, 2024)
Purpose: This study examines the impact of financial performance on the level of financial independence of hospitals using the effectiveness of the use of funds as a moderation.Research Methodology: This research uses quantitative methods with secondary data from 28 hospitals from 2021-2023. The hypothesis was tested on panel data with double regression analysis.Results: The test results showed that the profitability and activity ratio had a significant positive influence on the hospital's financial independence level, whereas the liquidity ratio did not significantly influence the hospital's financial independence level. The research also concluded that the effectiveness of the use of funds reinforces the positive influence of the profitability and liquidity ratios on the level of financial independence but weakens the positive relationship between the ratio of activity and the level of financial independence.Limitations: This research only used 3 proxies for the financial performance. It also did not conduct research on service performance due to the limitations of the research data obtained.Contribution: This study is expected to provide information that helps increase hospitals' financial independence so that the hospitals’ objectives can be achieved to the maximum.